Phacoemulsification: The first 50 Cases - Aneeq Ullah Baig Mirza, Aneeq Ullah Baig Mirza; Samina Jehangir, Samina Jehangir; Wasif Mohy-ud-din Kadri, Wasif Mohy-ud-din Kadri (Journal of Rawalpindi Medical College, 2007)
Background: To study and document the visual results, astigmatic changes and complications in first 50 cases of phacoemulsification. Methods: A study of first 50 cases of phacoemulsification performed by a single surgeon, was conducted in Eye Unit 1 of Services Hospital Lahore from January to June 1997. After proper case selection and thorough evaluation, phaco surgery was performed by either corneal or scleral tunnel technique. The incision size was kept at 5.5mm or 6.5mm depending upon the diameter of lens optic. The decision of suturing was made on the table. Postoperative examinations were conducted on day 1, week 1, week 3 and week 6 which included assessment of UCVA(uncorrected visual acuity), BCVA (best corrected visual acuity), complications and astigmatic changes. Results: Preoperative visual acuity ranged between hand movements and 6/18. On the first postoperative day, 24% of eyes attained a UCVA of 6/12 or better, while 48% of cases had a BCVA of 6/12 or better. One week after surgery, UCVA of 6/12 or better was present in 52% and BCVA of same magnitude in 68% of cases. At the end of sixth postoperative week, UCVA of 6/12 or better was seen in 84% and BCVA of same amount in 96% of eyes. The complications seen during the procedure were PC(posterior capsular) rent in one eye, PC rent with vitreous loss in 2 eyes and iris damage in 3 eyes. On the first postoperative day, striate keratopathy was seen in % of eyes. After 6 weeks, CME(cystoid macular edema) was seen in 5 eyes. The scleral tunnel 6.5mm sutured group was compared with the unsutured group for astigmatism. After 6 weeks, 62.5% of eyes in sutured group and 0% of eyes in unsutured group had > 2.0D(diopter) astigmatism (statistically significant). In sutured group, only 62.5% of eyes reverted to their preoperative meridian of astigmatism when examined after 6 weeks as compared to 90% of eyes in unsutured group. Conclusion: Phacoemulsification leads to an early visual rehabilitation with minimal complications and astigmatic changes, even in beginners if the procedure is followed meticulously.